Randomized trial of oral versus enteral feeding for patients with postoperative pancreatic fistula after pancreatoduodenectomy. Issue 3 (6th February 2019) - Wu, J.‐M.; Kuo, T.‐C.; Chen, H.‐A.; Wu, C.‐H.; Lai, S.‐R.; Yang, C.‐Y.; Hsu, S.‐Y.; Ho, T.‐W.; Liao, W.‐C.; Tien, Y.‐W.
Abstract : Background: Whether continued oral feeding may have a negative impact on healing of postoperative pancreatic fistula (POPF) is unclear. The aim was to test the hypothesis that oral feeding is non‐inferior to enteral feeding in closure of POPF after pancreatoduodenectomy, and to clarify the effects of oral feeding on the duration and grade of POPF. Methods: This multicentre, non‐inferiority randomized trial of oral or enteral feeding of patients with POPF after pancreatoduodenectomy recruited patients between August 2013 and September 2016. The primary efficacy outcome was the 30‐day fistula closure rate. The prespecified non‐inferiority margin was 15 per cent. Other efficacy outcomes included grade of fistula, and hospital stay and costs. Results: A total of 114 patients were included, and received oral (57) or enteral (57) feeding. The two groups were balanced in baseline characteristics and no patient was lost to follow‐up. In intention‐to‐treat analysis, oral feeding was non‐inferior to enteral feeding in terms of 30‐day fistula closure rate (88 versus 89 per cent respectively; difference –1·8 per cent, lower limit of 95 per cent c.i. –14·4 per cent; P = 0·020 for non‐inferiority). Compared with enteral feeding, oral feeding significantly reduced hospital costs and duration of stay. No significant differences were noted in the number of patients whose POPF evolved into grade B/C, or other outcomes. Conclusion: Oral feeding in patients with POPF after pancreatoduodenectomy did not increase the duration or grade of POPF, and was associated with reduced duration of stay and hospital costs. Registration number: NCT01755260 (http://www.clinicaltrials.gov ). Abstract : Both routes equivalent